Republic of Congo : Technical Assistance Report-National Accounts Mission. (IMF Staff Country Reports; Country Report, 2020)
This Technical Assistance report on the Republic of Congo presents mission outcomes and priority recommendations conducted to support the National Statistics Institute in its work on the national accounts estimates. The mission reviewed the calculation of consumption of fixed capital for the general government sector, an important element in calculating production by cost of production. The 2016 accounts are finalized and closed through the summary tables and the 2017 accounts are being finalized. The mission focused on an analysis of the 2016 and 2017 national accounts finalized in accordance with the 1993 System of National Accounts (SNA). The analysis consisted of a review of the information sources used, the methods of calculation and extrapolation, and compliance with the 1993 SNA. The mission made corrections and provided the team with an explanation of the consequences of the corrections and how to integrate them in the accounts, particularly the corrections affecting the branches' value added and, accordingly, gross domestic product. In order to facilitate progress in various areas of effort, the mission provided several priority recommendations focused on the urgency of preparing and validating a continuous, updated national accounts series. The mission proposes several corrections to the 2015 intermediate consumption matrix and recommends that the national accounting officers make the same corrections, proportionally, for 2016 and 2017.